An Intervention by and for Transgender Women Living With HIV: Study Protocol for a Two-Arm Randomized Controlled Trial Testing the Efficacy of “Healthy Divas” to Improve HIV Care Outcomes - Sevelius, Jae M.; Neilands, Torsten B.; Reback, Cathy J.; Castro, Danielle; Dilworth, Samantha E.; Kaplan, Rachel L.; Johnson, Mallory O. (Frontiers in Reproductive Health, 2021)
Introduction: Transgender women (assigned “male” at birth but who do not identify as male) are disproportionately impacted by HIV and experience unique barriers and facilitators to HIV care engagement. In formative work, we identified culturally specific and modifiable barriers to HIV treatment engagement among transgender women living with HIV (TWH), including prioritising transition-related healthcare over HIV treatment, avoiding HIV care settings due to gender-related and HIV stigma, concerns about potential drug interactions with hormones, and inadequate social support. Grounded in the investigators' Models of Gender Affirmation and Health Care Empowerment, we developed the Healthy Divas intervention to optimise engagement in HIV care among TWH at risk for treatment failure and consequential morbidity, mortality, and onward transmission of HIV. Methods and analysis: We conducted a 2-arm randomised controlled trial (RCT) of the intervention’s efficacy in Los Angeles and San Francisco to improve engagement in care among TWH (N=278). The primary outcome was virologic control indicated by undetectable HIV-1 level (undetectability = < 20 copies/mL), at baseline and follow-up assessment for 12 months at 3-month intervals. Ethics and dissemination: This study was approved by University of California, San Francisco Institutional Review Board (15-17910) and Western Institutional Review Board (20181370). Participants provided informed consent before enrolment in the study. We are committed to collaboration with National Institutes of Health officials, other researchers, and health and social services communities for rapid dissemination of data and sharing of materials. The results will be published in peer-reviewed academic journals and scientific presentations. We will make our results available to researchers interested in transgender health to avoid unintentional duplication of research, as well as to others in health and social services communities, including HIV clinics, LGBT community-based organisations, and AIDS service organisations.